Immunopathology in toxicology and drug development. Volume 1, - Parker, George A. (Humana Press, 2017)
This book provides a fundamental understanding of immunopathology and immunopathologic processes, with particular attention to nonclinical toxicology studies. Chapters provide an overview of general immunobiology, cells of the immune system, signaling and effector molecules, and immunopathology assays. A companion volume, Immunopathology in Toxicology and Drug Development: Volume 2, Organ Systems, offers summaries of organ-specific immunobiology and immunopathology as well as common responses to xenobiotics. These informative and strategic books were created in response to the large segment of drug development that focuses on chronic diseases, many of which involve alterations to the immune system. Therapies that target these diseases commonly involve some form of immunomodulation. As a result, the two volumes of Immunopathology in Toxicology and Drug Development are critical texts for individuals involved in diverse aspects of drug development. Readers will acquire a thorough understanding of immunopathology for detection and accurate interpretation of pathologic effects of xenobiotics on the immune system.- Resumé vydatel
Keywords: poruchy imunitního systému; xenobiotika; vývoj léčiv; immune system disorders; xenobiotics; drug development; elektronické knihy; sborníky; electronic books; papers of several authors